Spain : 2006 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Spain. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Spain showed strong growth performance marked by robust job creation and a solid fiscal position. Executive Directors supported the National Reform Program (NRP), which focuses on improving productivity, market flexibility, and competitiveness. They commended the appreciable fiscal surplus, pension reserve fund, and the public debt reduction. They welcomed the new Budget Stability Law (BSL), appreciated the Financial Sector Assessment Program (FSAP) assessment and the monetary stance of the Bank of Spain. They emphasized the need to regain competitiveness through the implementation of structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet